Synthesis of metal-free g-C3N4/GO nanocomposites for enhanced solar water splitting - Lee, Jun Yan (2015)
In today’s world, technology on harnessing renewable energy has become a great interest due to the environmental and energy crisis faced by the use of fossil fuels. Photocatalytic water splitting has become one of the areas that are studied intensively to generate hydrogen, as an alternative fuel, that is clean and sustainable. Metal free polymeric graphitic carbon nitride (g-C3N4) has emerged as one of the photocatalytic materials that are suitable for water splitting, however, the estimated quantum efficiency is very low. The purpose of this project is to investigate the effects of graphene oxide-graphitic carbon nitride (g-C3N4/GO) nanocomposite for enhanced photocatalytic hydrogen evolution. The g-C3N4 nanoparticles were synthesized via solvothermal method and subsequently, g-C3N4/GO nanocomposites were prepared using three different methods. Characterization techniques like fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), ultraviolet-visible spectroscopy (UV-vis), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were employed in this study. The as-synthesized GO/g-C3N4 samples appeared to give different morphologies and showed an improved photocatalytic H2 evolution as compared to the as-synthesized g-C3N4 nanoparticles under irradiation of UV-vis light.